Effects of Germination Duration on Milling, Physicochemical, and Textural Properties of Medium‐ and Long‐Grain Rice. Issue 1 (30th June 2015) - Han, Ashley; Arijaje, Emily O.; Jinn, Jia‐Rong; Mauromoustakos, Andy; Wang, Ya‐Jane
Abstract : Germinated brown rice is popular in Asia for its increased γ‐aminobutyric acid (GABA) content and sweeter and softer texture compared with conventional brown rice. However, most studies investigated germinated rice properties on medium‐grain or aromatic rice. The objective of this study was to compare differences between a medium‐grain (Jupiter) and a long‐grain (Wells) rice under similar germination conditions on their milling, physicochemical, and textural properties over the course of germination. Rough rice was soaked in water at 25°C for 12 h and then incubated at 30–34°C for four germination durations. Wells had a higher breakage percentage and a greater weight decrease than Jupiter during germination. Wells had a significantly lower GABA content before germination and at the first two germination durations than Jupiter, but the GABA content in Wells significantly increased at the third germination duration to become significantly higher than that of Jupiter. There were no significant changes in gelatinization temperatures and pasting properties of germinated rice from both cultivars at different germination durations. The cooked rice hardness from Wells decreased at the longest germination duration, whereas Jupiter showed a more significant decrease in cooked rice stickiness from germination. The results demonstrate that the impacts of germination on physical, chemical, and textural properties of rice were affected by grain type and germination duration.